A brain death model with slow induction for experimental studies of organ donation - P. A. Ermolaev; T. P. Khramykh; A. S. Vyaltsin; L. O. Barskaya (Сеченовский вестник, 2024)
Aim. To test in experiment a pathogenetically adequate model of brain death due to increased intracranial pressure with gradual induction, allowing the evaluation of the changes occurring in the organs of a potential donor.Materials and methods. 6–8 months old outbred male rats of the experimental group (n = 18) and the control group (n = 8) were anesthetized, the left common carotid artery was catheterized to record systolic, diastolic blood pressure (BP) and heart rate (HR), the mean BP (MBP) was calculated. After transfer to artifi cial ventilation, brain death was simulated in the experimental group using the developed method.Results. All animals in the experimental group suffered brain death 30 minutes from the start of the experiment;10 rats (56%) died within 3 hours due to progression of circulatory failure. Initially, in anesthetized animals, MBP was 101 (90; 105) mm Hg, HR 310 (297; 315) beats/min. After 5 minutes from the start of brain death induction, MBP increased to 147 (140; 150) mm Hg (p = 0.01), HR to 396 (384; 406) beats/min (p = 0.03). Further, within 20 minutes there was a decrease in MBP to 94 (90; 100) mm Hg and HR to 290 beats/min. During the observation period from 26 to 90 minutes, there was a stabilization of MBP at the level of 87–92 mm Hg, there was a tendency to bradycardia with HR from 263 to 274 beats/min (p = 0.01). Then after 120–150 minutes from the beginning of brain death induction, MBP continued to decrease to 75–80 mmHg (p = 0,03), HR to 256–264 beats/min (p = 0,01). At the end of the experiment, despite volemic support, MBP decreased to 64 (61; 67) mm Hg (p = 0.02), bradycardia worsened with HR to 250 (248; 260) beats/min (p = 0.01), indicating the hemodynamic decompensation.Conclusion. The results of experimental testing of an animal brain death model on outbred rats showed that this model is pathogenetically adequate and useful to assess the condition of potential donor organs within 3 hours after the induction of brain death.